Legal Review of the Validity of Private Agreements Regarding Secured Movable Property in Fiduciary Agreements - Maryani, Halimatul; Halim, Abdul (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
With the development of transportation and existing technology, many payment methods for various needs have emerged. One rapidly growing need is for transportation facilities, which often have costs that are not easily accessible to many people. Non-bank financial institutions have emerged as an effort to facilitate consumers in meeting their increasingly diverse needs. These institutions, which assist with all types of consumer transactions, are rapidly developing and are particularly popular among consumer financing institutions. Based on the legal research conducted, it can be explained that the rights and obligations of consumers are to make installment payments according to the payment schedule, while the rights and obligations of the consumer financing institution are to pay the payment amount to the supplier and repossess the motorcycle used as collateral in consumer financing in the event of default. In the case of default, compensation, contract cancellation, or risk related to force majeure must be provided.